The Relationship Between Family Functioning and Internalizing Problems in Chinese Adolescents: A Moderated Mediation Model - Wang, Qiuying; Peng, Siya; Chi, Xinli (Frontiers in Psychology, 2021)
Research has consistently found that poor family functioning is a risk factor for adolescents' internalizing problems. However, studies of the mediating and moderating mechanisms underlying this relation are insufficient. In this study, we explore the association between family functioning and adolescents' internalizing problems by testing the mediating roles of positive youth development (PYD) attributes and the moderating role of migrant status. A large cross-sectional sample of 11,865 Chinese adolescents (mean age = 14.45 years, standard deviation = 1.55 years) were used to measure internalizing problems, family functioning, PYD, migrant status, and other demographic information. After controlling for covariates (age, gender, grade, and socioeconomic status), the results revealed that PYD mediated the relation between family functioning and internalizing problems. Moreover, migrant status moderated the relationship between family functioning and internalizing problems. Specifically, the effects of family functioning on internalizing problems were stronger among local-born adolescents than among migrant adolescents. The findings indicate that improving family functioning and PYD attributes may be promising approaches to prevent/reduce adolescent internalizing problems.